The crystal structure of 4-(chloromethyl)benzonitrile, C8H6ClN - Miao Mingzhi; Li Ji (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C8H6ClN, orthorhombic, Pnma (no. 62), a = 20.3965(7) Å, b = 7.8164(3) Å, c = 4.5015(2) Å, V = 717.66(5) Å3, Z = 4, Rgt(F) = 0.0265, wRref(F2) = 0.0670, T = 100.0 K.